Intradermal methylene blue analgesic application in posthemorrhoidectomy pain management: a randomized controlled trial - Azhough, Ramin; Jalali, Pooya; Dashti, Mohammad Reza; Taher, Sahar; Aghajani, Ali (Frontiers in Surgery, 2024)
Introduction: Unbearable post-hemorrhoidectomy pain is a well-documented challenge, significantly impacting patient well-being and satisfaction after surgery, often influencing patients to decline in undergoing this procedure. It is widely recognized that methylene blue has an effect of reducing inflammation and pain by reduces the production of nitric oxide and inhibiting the action potentials production in nervesmethylene blue, traditionally recognized as a biological dye, extends beyond its conventional application, demonstrating disinfectant properties. This study aims to explore the potential benefits of postoperative regional administration of methylene blue in providing extended relief from post-hemorrhoidectomy pain.Methods: This study included 97 patients aged 18-75 undergoing hemorrhoidectomy for stage III or IV hemorrhoids. A double-blind, randomized controlled trial compared postoperative intradermal injections of 1% methylene blue to 0.5% Marcaine as the control group. Two-week follow-up assessed pain. Statistical analysis, adherence to ethical standards, and registration were conducted.Result: No significant differences were found in baseline demographics, surgical parameters, or complications between the Methylene Blue and control groups. Intervention group remained lower in mean pain score until the 12 th day. Methylene blue group reported significantly lower postoperative pain scores from days 1 to 7, with no significant differences afterward.Conclusion: This ongoing randomized controlled trial reveals the potential analgesic benefits of intradermal injection 1% methylene blue. It demonstrates comparable efficacy in reducing posthemorrhoidectomy pain, with negligible side effects and complications.